2019
DOI: 10.1016/j.isci.2019.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Diet, Microbiota, and Colorectal Cancer

Abstract: The intestinal epithelium is a very dynamic tissue under a high regenerative pressure, which makes it susceptible to malignant transformation. Proper integration of various cell signaling pathways and a balanced cross talk between different cell types composing the organ are required to maintain intestinal homeostasis. Dysregulation of this balance can lead to colorectal cancer (CRC). Here, we review important insights into molecular and cellular mechanisms of CRC. We discuss how perturbation in complex regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 166 publications
0
23
0
Order By: Relevance
“…Studies have shown that even the same species of gut bacteria may have different impacts. For instance, the enterotoxigenic strain of B. fragilis may serve as a trigger for colitis and tumorigenesis, while the non-toxigenic strain of B. fragilis may serve as an antiinflammatory probiotic and protect against colitis and CRC (11). Thus, it remains a formidable task to elucidate the association between dysbiosis of gut bacteria and diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that even the same species of gut bacteria may have different impacts. For instance, the enterotoxigenic strain of B. fragilis may serve as a trigger for colitis and tumorigenesis, while the non-toxigenic strain of B. fragilis may serve as an antiinflammatory probiotic and protect against colitis and CRC (11). Thus, it remains a formidable task to elucidate the association between dysbiosis of gut bacteria and diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, inflammatory bowel disease (IBD), a devastating inflammatory disease of the gut, is also very high in developed countries (6,7), and IBD greatly increased the risk of CRC with a hazard ratio as high as 33.3 (5), suggesting a likely intimate link between CRC and IBD (8)(9)(10). Recently, dysbiosis of microbiota in the development of IBD and CRC has drawn more and more attention (11)(12)(13)(14)(15). Accumulating evidence suggests that dysbiosis of gut microbiota, gut inflammation, and CRC may have intimate interaction and connection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…mTORC1 is a nutrient sensor that influences cell growth and proliferation in-vivo . Nutrients, stress signals such as hypoxia and glucose deprivation, growth factors (GFs) as well as cellular energy status are upstream signals that impact on mTORC1 activity ( 143 ). The activity of mTOR1 is essentially dependent on the integration of GF and nutrient signals.…”
Section: Introductionmentioning
confidence: 99%
“…The activity of mTOR1 is essentially dependent on the integration of GF and nutrient signals. The activation of mTORC1 impact on cellular processes, including nucleotide, protein, and lipid synthesis, cellular metabolism such as ATP production, and autophagy, thereby functioning to maintain balance between anabolic and catabolic processes ( 143 ). Activities such as translational machinery that promotes growth and proliferation through the phosphorylation of ribosomal protein S6 kinase (S6K) and the eukaryotic translation initiation factor 4E(elF4E)-binding protein (4EBP).…”
Section: Introductionmentioning
confidence: 99%